2020
DOI: 10.1039/d0cb00086h
|View full text |Cite
|
Sign up to set email alerts
|

Sub-stoichiometric inhibition of IAPP aggregation: a peptidomimetic approach to anti-amyloid agents

Abstract: Naphthalimide-appended oligopyridylamide peptidomimetic modulate islet amyloid polypeptide amyloidogenesis and disaggregate preformed oligomers and fibrils into non-toxic conformations at substoichiometric concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 60 publications
1
37
0
Order By: Relevance
“…This suggests the ability of LUVs to decrease the effectiveness of the small molecule inhibitors is less related to structural changes and instead presumably a result of decreased availability due to partitioning between the lipid membrane and surrounding solvent. Given both amyloid proteins and small molecule inhibitors will partition between the lipid membrane and surrounding solvent to varying degrees, and since solution aggregation mechanisms are different to those on the bilayer [20,73], this partitioning behaviour is likely to be a significant contributor to variations in inhibitor efficacy for specific protein, inhibitor and lipid composition combinations by altering the extent of proteininhibitor interactions [41,74].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests the ability of LUVs to decrease the effectiveness of the small molecule inhibitors is less related to structural changes and instead presumably a result of decreased availability due to partitioning between the lipid membrane and surrounding solvent. Given both amyloid proteins and small molecule inhibitors will partition between the lipid membrane and surrounding solvent to varying degrees, and since solution aggregation mechanisms are different to those on the bilayer [20,73], this partitioning behaviour is likely to be a significant contributor to variations in inhibitor efficacy for specific protein, inhibitor and lipid composition combinations by altering the extent of proteininhibitor interactions [41,74].…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent work with hIAPP, a membrane-associated amyloidogenic protein, proposed that partitioning of hIAPP and small molecule inhibitors (based on an oligopyridylamide scaffold) between a membrane and solution altered inhibitor efficacy in a manner dependent on the hydrophobicity of the inhibitor [40]. In addition, some inhibitors, including resveratrol, have been shown to influence structural changes in hIAPP that are thought to prevent membrane association of the polypeptide, thereby preventing lipid catalysed aggregation and membrane disruption [41][42][43]. To better develop effective small molecule inhibitors of misfolding and aggregating proteins, we must therefore understand their interactions in the physiological environments in which these inhibitors will be acting.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we performed two‐dimensional HSQC NMR analysis of recombinant IAPP (having an amide‐free C terminus) with CB[7] to identify its binding sites on the protein (Figure 3). Following published literature, we assigned the chemical shifts of the different residues in 15 N labeled IAPP [8b,30] . We observed that residues at the N terminus were perturbed at 2 equivalents of CB[7], while those at the C terminus were mostly unchanged.…”
Section: Figurementioning
confidence: 99%
“…Molecular chaperones such as heat shock proteins (HSPs) defend against neurodegenerative diseases by suppressing formation of the amyloid and clearing the misfolded species. , A more realistic AD therapeutic strategy might involve maintaining Aβ 42 in its nontoxic monomeric form, disintegrating oligomers, and clearing the misfolded proteins. We have previously reported the development of different peptidomimetic strategies for targeting protein–protein interactions. Recently, we have shown that oligo-pyridylamide-based peptidomimetics inhibit amyloid-beta oligomerization and fibrillation by constraining the peptide into a nontoxic helical structure. , With the aim of expanding the toolkit of peptidomimetic scaffolds, we set out to explore new strategies for modulation of amyloid-beta fibrillation. In this study, we have designed a small library of cationic N-substituted oligo-pyrrolamides for inhibition of amyloid-beta fibrillation (Figure S1).…”
Section: Introductionmentioning
confidence: 99%